Clinical performance of class II MOD fiber reinforced resin composite restorations: an 18-month randomized controlled clinical trial - Mohamed Hamdy Mohamed; Eman Ali Abouauf; Rania Sayed Mosallam (BMC Oral Health)
Abstract Background In recent years, there have been suggestions for new restorative strategies that aim to effectively utilize modern adhesive technologies and protect the remaining intact tooth structure. This study was conducted to evaluate the clinical performance of fiber reinforced resin composites in restoring Class II MOD cavities over 18 months. Methods Forty-five participants with class II MOD cavities were randomly enrolled. The participants were allocated to three groups (n = 15): Group (1) short glass fiber reinforced resin composite (EverX Posterior), Group (2) polyethylene fiber (Ribbond-Ultra) reinforced resin composite and Group (3) only conventional resin composite (Filtek Z250). The modified USPHS criteria were used to evaluate the restorations at baseline; and at three, six, 12 and 18 months. The categorical data were reported as frequencies and percentages. Intergroup comparisons were analyzed using Chi-Square test after Bonferroni correction (P ≤ 0.016). Comparisons within each group were analyzed using Cochran’s Q test after Bonferroni correction (P ≤ 0.005). Results Intergroup comparisons revealed no statistically significant differences in any of the evaluated criteria except for color match. Compared with the other groups, the short glass fiber-reinforced restoration group presented significantly fewer color matches at different follow-up periods. Conclusions Class II direct fiber-reinforced resin composite restorations can offer acceptable performance similar to the nanohybrid resin composite through 18-month of clinical service. Clinical significance Fiber reinforcement of resin composites could be a reliable technique for restoring posterior cavities considering factors such as application complexity, cost and aesthetic considerations. Trial registration The trial was registered retrospectively on (19/05/2022) at https://clinicaltrials.gov with the ID (NCT05380973).